Determinants of Self-Rated Health Among Middle-Aged and Elderly Patients with COPD: The China Health and Retirement Longitudinal Study. (January 2022) - Wang, Cui; Wang, Limin; Hou, Luoya; Lu, Han; Shang, Shaomei
This study aimed to assess self-rated health (SRH) status and its determinants in patients with chronic obstructive pulmonary disease (COPD). Participants aged at least 45 years were included from a nationally representative investigation in 2015. The SRH assessment was divided into two groups: "good" and "not good." Independent samples t -tests, chi-square tests, and Fisher's exact tests were used to determine differences in patient characteristics between the two groups. Multiple logistic models were used to determine factors influencing SRH. A total of 1, 215 patients with COPD were included in the final analysis, of whom 21.2% reported favorable SRH status. The results indicated that female gender, non-smoking, and elevated peak expiratory flow correlated with better SRH, while nighttime sleep duration less than 7 hours, asthma, and disability, negatively impacted SRH. Our findings provide new evidence for the development of effective health promotion programs for the well-being of patients with COPD.